Healthcare and Indirect Cost of the Laparoscopic vs. Vaginal Approach in Benign Hysterectomy - Martínez-Maestre, María A.; Jódar-Sánchez, Francisco; Calderón-Cabrera, Ana M.; González-Cejudo, Carmen; Silván-Alfaro, José M.; Melero-Cortés, Lidia María (Society of Laparoscopic & Robotic Surgeons, 2022)
Background and objectives: The aim of this study was to analyze indirect costs of vaginal and laparoscopic routes for hysterectomy to determine whether this makes a difference in total costs when considering route for surgery. Methods: A five-year observational retrospective cohort study was conducted in an academic tertiary care center. A total of 517 patients scheduled for total laparoscopic hysterectomy (n = 137) and vaginal hysterectomy (n = 380) for benign conditions between January 1, 2008 and December 31, 2012 meeting inclusion criteria were reviewed. Results: Indirect costs were higher in the vaginal hysterectomy group compared to the laparoscopic hysterectomy group (mean cost €3,239.86 vs. €1,371.58; cost increase of €1,868.28; p <0.001). Indirect costs due to lost-work-productivity were the most important, represented by 97.7% in the vaginal group and 93.6% in the laparoscopic group. Conclusion: Among women undergoing hysterectomy for benign disease, laparoscopic hysterectomy appears to be superior to vaginal hysterectomy when indirect costs are analyzed in a five-year temporal horizon. Laparoscopic hysterectomy is a good alternative to vaginal hysterectomy when technically feasible as both present comparable advantages. The surgical approach to hysterectomy should be decided in light of the relative benefits and hazards, which will depend on clinical circumstances and surgical expertise.
Keywords: Útero - Cirugía - Costes; Enfermedad ginecológica; Coste sanitario; Coste indirecto; Cirugía laparoscópica